Type I and Type II Photosensitized Oxidation Reactions: Guidelines and Mechanistic Pathways - Baptista, Maurício S. (2017)
Here, 10 guidelines are presented for a standardized definition of type I and type II photosensitized oxidation reactions. Because of varied notions of reactions mediated by photosensitizers, a checklist of recommendations is provided for their definitions. Type I and type II photoreactions are oxygen-dependent and involve unstable species such as the initial formation of radical cation or neutral radicals from the substrates and/or singlet oxygen (1O2 1∆g) by energy transfer to molecular oxygen. In addition, superoxide anion radical (O.- 2) can be generated by a charge-transfer reaction involving O2 or more likely indirectly as the result of O2-mediated oxidation of the radical anion of type I photosensitizers. In subsequent reactions, O.- 2 may add and/or reduce a few highly oxidizing radicals that arise from the deprotonation of the radical cations of key biological targets.O.- 2 can also undergo dismutation into H2O2, the precursor of the highly reactive hydroxyl radical (.OH) that may induce delayed oxidation reactions in cells. In the second part, several examples of type I and type II photosensitized oxidation reactions are provided to illustrate the complexity and the diversity of the degradation pathways of mostly relevant biomolecules upon one-electron oxidation and singlet oxygen reactions.